Body mass explains digestive traits in small vespertilionid bats - Cabrera Campos, Iván (2021)
Bats are unique among mammals in that they have evolved the capacity to fly. This has generated strong selective pressure on the morphology and function of their digestive system. Given that in bats intestinal length and nominal surface-area are proportional to body mass, this trait importantly relates to explaining some of their digestive characteristics. We described the relationship between digestive traits and body mass of four species of bats of the family Vespertilionidae living in a montane ecosystem in central Mexico. We calculated food transit time, apparent dry matter digestibility, and defecation rate in feeding trials under captive conditions. We also: (1) built a model of the relationship between digestive traits and body mass to determine if this association was consistent within the members of the family Vespertilionidae, and (2) mapped these traits along the phylogeny to explore how digestive characteristics may have evolved. In our feeding trials, body mass was positively related to transit time and negatively related to apparent dry matter digestibility. The model predicted accurately the transit time in bats with body mass < 20 g. The phylogenetic approach suggested that over the evolutionary history of the family, transit time decreased as digestibility increased. Because of the results obtained here, it is likely that for most bats of the family Vespertilionidae, adaptations in digestive traits to process food have followed evolutionary changes in their body mass. We discuss these findings in a physiological and ecological context.